1990
DOI: 10.7557/2.10.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic inclusion bodies associated with vesicular ulcerative and necrotizing lesions of the digestive mucosa in fallow deer (Dama dama L.)

Abstract: Intracytoplasmic epithelial inclusion bodies in the digestive mucosa of fallow deer (Dama dama L.) were found to most probably be the result of an unspecific degenerative or post mortal change. There are reasons to believe that this is true also for the inclusion bodies found in reindeer, roe deer and moose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similar IB have been reported in an outbreak of a disease resembling BVD in farmed fallow deer (Diaz et al } 1988). To reveal the origin of the IB a study was performed by Diaz et al (1990) to see if other injuries, besides virus diseases, such as autolysis could play a role in the genesis of the IB. They concluded that IB could be a result of unspecific degenerative or post-mortal changes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar IB have been reported in an outbreak of a disease resembling BVD in farmed fallow deer (Diaz et al } 1988). To reveal the origin of the IB a study was performed by Diaz et al (1990) to see if other injuries, besides virus diseases, such as autolysis could play a role in the genesis of the IB. They concluded that IB could be a result of unspecific degenerative or post-mortal changes.…”
Section: Discussionmentioning
confidence: 99%